2022
DOI: 10.1002/prop.202200001
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Motion near Black Hole and Cosmological Horizons

Abstract: It is known that certain types of particle motion near black hole horizons are chaotic while it has been proposed the existence of a universal bound for their Lyapunov exponent. We discuss the relation between chaos and inaffinity in presence of black hole and cosmological horizons. We argue that although a relation between the Lyapunov exponent and the generalized surface gravity appears naturally, in general there is no reason for the Lyapunov exponent of classical trajectories to be bounded in generic space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…By itself this is not surprising: a local instability can lead to a growing mode even in a trivially integrable system, the simplest example being the inverse chaotic oscillator [57]. This is similar to findings of [31] where it is noted that horizons are really sources of instability in the bulk. Even integrable systems can display local instability in the vicinity of thermal horizons.…”
Section: Jhep04(2024)025supporting
confidence: 67%
See 2 more Smart Citations
“…By itself this is not surprising: a local instability can lead to a growing mode even in a trivially integrable system, the simplest example being the inverse chaotic oscillator [57]. This is similar to findings of [31] where it is noted that horizons are really sources of instability in the bulk. Even integrable systems can display local instability in the vicinity of thermal horizons.…”
Section: Jhep04(2024)025supporting
confidence: 67%
“…In our first example we closely follow the idea of [31] and study bulk motion in a broad class of bulk geometries: hyperscaling-violating horizons at finite temperature, constructed in [58][59][60][61] as gravity duals of effective field-theories with scaling and long-range entanglement, thought to be ubiquitous in quantum-many body systems. In [31], it is shown that the bulk geodesics, i.e.…”
Section: General Hyperscaling-violating Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the geodesic in a black hole can be chaotic, and this black hole chaos has been researched in [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. According to Hashimoto and Tanahashi [26], it is assumed that the Lyapunov exponent of a particle in a black hole has an upper bound near the horizon.…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity is represented by a Lyapunov exponent. A lot of work has been done on the chaos and exponent [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Focusing on the near-horizon region of the black hole, Hashimoto and Tanahashi studied the chaos generated by the radial motion of the particle [30].…”
Section: Introductionmentioning
confidence: 99%